2006
DOI: 10.1007/s00270-005-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tumors: Technical Success and Early Clinical Experience with Radiofrequency Ablation of 18 Tumors

Abstract: Our early experience with percutaneous image-guided radiofrequency ablation demonstrates it to be a feasible, safe, noninvasive, and effective treatment of small peripheral renal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To address this question, we conducted a metaanalysis to see if Zagoria 26 Weizer 20 Veltri 41 Varkarakis 25 Ukimura 40 Silverman 22 Shingleton 39 Shingleton 38 Sabharwal 37 Roy-Choudhury 36 Pavlovich 35 Ogan 34 Mogami 28 Miki 33 Merkle 23 Memarsadeghi 32…”
Section: Discussionmentioning
confidence: 99%
“…To address this question, we conducted a metaanalysis to see if Zagoria 26 Weizer 20 Veltri 41 Varkarakis 25 Ukimura 40 Silverman 22 Shingleton 39 Shingleton 38 Sabharwal 37 Roy-Choudhury 36 Pavlovich 35 Ogan 34 Mogami 28 Miki 33 Merkle 23 Memarsadeghi 32…”
Section: Discussionmentioning
confidence: 99%
“…Other indications include coexistent morbidity or a palliative situation, high surgical or anesthetic risk, and solitary kidney [36,37]. While Mejean and co-workers [35] advocate the use of thermal ablation in renal tumors remote from the renal collecting system, this view is challenged by Gervais and co-workers [38], who treated 100 renal tumors in 85 patients by means of RFA and found that direct contiguity of renal tumor or zone of ablation to the renal collecting system did not increase the complication rate.…”
Section: Distant Metastasis Of Rccmentioning
confidence: 99%
“…A number of clinical series have shown favorable shortterm results, 7,9,10 although there remains some concern about the degree of tumor destruction. Both CT and MRI are used routinely during follow-up of ablated lesions, and image interpretation is a crucial component to identify malignant recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…7 The technique has been successful in ablating tumors in a wide variety of organs. Preliminary results with favorable short-term tumor-free recurrence and survival rates have been reported for renal-cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%